The effects of bank size and funding liquidity on financial stability: does bank regulation matter? evidence from BRICS - Mahat, Fauziah; Dahir, Ahmed Mohamed (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
This paper investigates whether the effect of funding liquidity on financial stability changes depending upon bank regulation and bank size, using bank-level data for 254 banks in BRICS over the period 2005-2014. The paper employs the system GMM techniques on dynamic panel analysis. The results show that the effect of funding liquidity on financial stability is positively and negatively associated with bank regulation and bank size, respectively, suggesting that bank regulation improves the financial stability, while the size hurts the stability. Moreover, the impact of funding liquidity on stability is strongly pronounced following the 2008 crisis. These findings provide further insights about bank regulation and bank size.